Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/pme.12376
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Caregivers and Patients Regarding Opioid Analgesic Use in Terminal Care

Abstract: These patients and caregivers demonstrated a preference for pain alleviation by opioid treatment and gave negative assessments on adverse digestive effects that can cause this treatment to be abandoned. They expressed interest in receiving more information and in participating in therapeutic decision making, and they reported erroneous beliefs and a lack of information about the effects of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] vealed that the best approach was unknown. 47 Of the remaining 14 studies, 6 (42.9%) identified patient preferences for the purpose of guideline development, [40][41][42]49,50,53 and 10 (71.4%) explored various methods for doing so. 38,39,[43][44][45][46][47][48]51,52…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] vealed that the best approach was unknown. 47 Of the remaining 14 studies, 6 (42.9%) identified patient preferences for the purpose of guideline development, [40][41][42]49,50,53 and 10 (71.4%) explored various methods for doing so. 38,39,[43][44][45][46][47][48]51,52…”
Section: Search Resultsmentioning
confidence: 99%
“…49 Two studies identified preferences by focus group, 48,52 and 2 studies employed focus groups plus Delphi consensus process 40 or questionnaire. 41 Two studies identified preferences with interviews, 44,50 and 1 study combined interviews with a questionnaire. 51 One study employed a questionnaire only, 42 and 1 study used only a RAND consensus process.…”
Section: Identifying Patient Preferencesmentioning
confidence: 99%
“…Despite the availability of the drugs, inadequate pain management has been found among cancer patients [3, 4]. One of the most frequent causes of undertreatment is misconceptions about opioids [58]. …”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study revealed that many patients and families believed that opioids should be only used in terminal cases and at the end of life, and that opioid use may be associated with premature death [5]. Another study that attempted to identify the barriers to cancer pain management in Taiwan demonstrated that informed family caregivers of advanced cancer patients had concerns about reporting pain and administering opioids, particularly as they related to disease progression and possible side effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…A key factor in uencing this decision, though rarely mentioned by participants, is the role the health care provider serves in informing that decision. Patients often structure their decisions by considering the opinions and suggestions of their healthcare providers 24 . Providers should discuss the trade-offs of pain medication with their patients before the patients decide about whether to take the drug.…”
Section: Main Ndingsmentioning
confidence: 99%